2020
DOI: 10.18196/jai.2102151
|View full text |Cite
|
Sign up to set email alerts
|

Determining Factors of Cloud Computing Adoption: A Study of Indonesian Local Government Employees

Abstract: Research aims: This study aims to identify the factors that influence the Indonesian local government employees to adopt cloud computing. Design/Methodology/Approach: A Unified Theory of Acceptance and Use of Technology (UTAUT) theory were employed to identify these factors. Research data were obtained using an online survey of employees, working in local governments in Indonesia. This study obtained 123 responses, which were then processed utilizing the structural equation modeling approach. Research findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
(79 reference statements)
1
15
0
1
Order By: Relevance
“…Organizational models that will help in adopting cloud services (Mohammed et al, 2017b;Salam & Ali, 2020;Shafique et al, 2017). They specify the determinants to be considered for cloud adoption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational models that will help in adopting cloud services (Mohammed et al, 2017b;Salam & Ali, 2020;Shafique et al, 2017). They specify the determinants to be considered for cloud adoption.…”
Section: Discussionmentioning
confidence: 99%
“…According to most studies, the elements related to the adoption of cloud services fall into three main categories of technological, organizational, and environmental levels (Ali et al, 2015;Ji & Liang, 2016;Polyviou & Pouloudi, 2015;Shafique et al, 2017). However, some studies evaluated the factors based on behavioral factors like performance expectancy, social influence, facilitating conditions, perceived risk, trust, and security (Alrashed & Alotaibi, 2017;Lian, 2015;Salam & Ali, 2020;Sivathanu, 2018). Other researchers considered different elements.…”
Section: Discussionmentioning
confidence: 99%
“…In the Indonesian local government scenario, Salam and Ali [16] attempted to unravel the factors that impact the employees' adoption of cloud computing, by applying the Unified Theory of Acceptance and Use of Technology (UTAUT) theory. The study covered 123 respondents and applied SEM for data analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study also found that the predictors can be divided into constructs or categories. Previous studies found that reliability and trust are important predictors of the usage of CBEG [20], [26]. Other studies refer to the importance of security in the usage of the CBEG [24].…”
Section: Discussionmentioning
confidence: 99%
“…The study proposed a security trust model for Cloudlet for E-government web services. [26] Indonesia/local government Questionnaire Performance expectancy and expectation availability have positive effects. [20] Developing countries/issue and challenges of adoption of CBEG Review IT infrastructure, availability and trust are critical for the use of CBEG.…”
Section: Case Studymentioning
confidence: 99%